2004
DOI: 10.1063/1.1737142
|View full text |Cite
|
Sign up to set email alerts
|

The (n,γ) cross sections of short-living s-process branching points

Abstract: Abstract. An experimental method to determine the (n,γ) cross section of short-living s-process branching points using data of the inverse (γ,n) reaction is presented. The method was used to observe the branching point nucleus 95 Zr because the elemental abundance patterns corresponding to this branching point cannot be reproduced by full stellar models and a possible error source is the neutron capture cross section of 95 Zr. The analysis of the experiment is still under progress, we will outline the curren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For r-process studies, nuclear quantities such as β -decay properties, masses, and neutron capture rates for nuclei far from the so-called valley of stability are of key importance and are still an experimental challenge 29 . One example for a suitable initial isotope for the investigation of multi-neutron capture events in the r-process chain, but also in the s-process scheme is the stable 96 Zr isotope 30 , 31 . Chen et al 31 have shown in simulations that for multiple neutron capture processes, a neutron peak-flux of 10 24 n/(cm 2 s) is required to ensure the neutron capture time (≈1 s) shorter than the 97−102 Zr isotope half-lives.…”
Section: Introductionmentioning
confidence: 99%
“…For r-process studies, nuclear quantities such as β -decay properties, masses, and neutron capture rates for nuclei far from the so-called valley of stability are of key importance and are still an experimental challenge 29 . One example for a suitable initial isotope for the investigation of multi-neutron capture events in the r-process chain, but also in the s-process scheme is the stable 96 Zr isotope 30 , 31 . Chen et al 31 have shown in simulations that for multiple neutron capture processes, a neutron peak-flux of 10 24 n/(cm 2 s) is required to ensure the neutron capture time (≈1 s) shorter than the 97−102 Zr isotope half-lives.…”
Section: Introductionmentioning
confidence: 99%
“…For r-process studies nuclear quantities such as β-decay properties, masses and neutron capture rates for nuclei far from the so-called valley of stability are of key importance and are still an experimental challenge today [25]. One example of an suitable initial isotope for the investigation of multi-neutron capture events in the r-process chain, but also in the s-process scheme is the stable 96 Zr isotope [26,27]. In [27] it was demonstrated that for multiple neutron capture processes, a neutron peak-flux of 10 24 n/(cm 2 s) is required to ensure the neutron capture time (≈1 s) shorter than the 97−102 Zr isotope half-lives.…”
Section: Introductionmentioning
confidence: 99%